The Effects of Aging on Male Mouse Pancreatic β-Cell Function Involve Multiple Events in the Regulation of Secretion: Influence of Insulin Sensitivity. Issue 3 (25th September 2021) - Tudurí, Eva; Soriano, Sergi; Almagro, Lucía; García-Heredia, Anabel; Rafacho, Alex; Alonso-Magdalena, Paloma; Nadal, Ángel; Quesada, Ivan
Abstract: Aging is associated with a decline in peripheral insulin sensitivity and an increased risk of impaired glucose tolerance and type 2 diabetes. During conditions of reduced insulin sensitivity, pancreatic β cells undergo adaptive responses to increase insulin secretion and maintain euglycemia. However, the existence and nature of β-cell adaptations and/or alterations during aging are still a matter of debate. In this study, we investigated the effects of aging on β-cell function from control (3-month-old) and aged (20-month-old) mice. Aged animals were further categorized into 2 groups: high insulin sensitive (aged-HIS) and low insulin sensitive (aged-LIS). Aged-LIS mice were hyperinsulinemic, glucose intolerant, and displayed impaired glucose-stimulated insulin and C-peptide secretion, whereas aged-HIS animals showed characteristics in glucose homeostasis similar to controls. In isolated β cells, we observed that glucose-induced inhibition of KATP channel activity was reduced with aging, particularly in the aged-LIS group. Glucose-induced islet NAD(P)H production was decreased in aged mice, suggesting impaired mitochondrial function. In contrast, voltage-gated Ca 2+ currents were higher in aged-LIS β cells, and pancreatic islets of both aged groups displayed increased glucose-induced Ca 2+ signaling and augmented insulin secretion compared with controls. Morphological analysis of pancreas sections also revealed augmented β-cell mass with aging, especially in the aged-LIS group, as well as ultrastructural β-cell changes. Altogether, these findings indicate that aged mouse β cells compensate for the aging-induced alterations in the stimulus-secretion coupling, particularly by adjusting their Ca 2+ influx to ensure insulin secretion. These results also suggest that decreased peripheral insulin sensitivity exacerbates the effects of aging on β cells.